Control gubernamental y la gestión contable en la Gerencia Sub Regional de Ucayali Contamana año 2022 - Jaramillo Durand, Brenda Belkis (2022)
The objective of the study was to determine the relationship between government control and accounting management in the Sub Regional Management of Ucayali Contamana Year 2022, where an applied type research, descriptive level and non-experimental design was chosen, in which it was taken as a sample to 89 workers, similar, the technique of the survey was used as an instrument the questionnaire to collect the information. According to the results, it is evident that government control is regular, because it almost always demonstrates independence from management and exercises supervision of internal control; In addition, it sometimes defines the objectives with clarity that allows the identification and evaluation of related risks. For its part, the accounting management has been developing efficiently, thanks to the fact that international standards are respected regarding the registration of assets, liabilities and equity, in turn detailed and summarized information is provided on the accounting activity, impaired faithful data and economic facts complete and free of error. Finally, it will be prolonged that there is a significant relationship between government control and accounting management, contrasted by the Pearson coincidence statistic, which shows a coefficient of 0.938, which is a very strong positive level, and a significance of 0.000.